The Flag on the Hilltop - Earle, Mary Tracy, 1864-1955 (Book collections on Project MUSE., 2013)
Mary Tracy Earle occupies an unusual place among southern Illinois fiction writers: the descendent of a family that helped shape the region, she left her hometown of Cobden and made her way to New York City where she published two novels and saw her short stories printed in the best magazines of the day-including The Saturday Evening Post, Harper's, and The Atlantic Monthly. She succeeded so well at her craft that she is still identified in some literary histories as "a New York writer"--a phenomenon that may help to explain why she is not particularly well known in her native area.